HOW MAGNETOTELLURICS IS ABLE TO SEE THROUGH 3D NEAR-SURFACE INHOMOGENEITIES? - Szarka L.; Ádám A.; Zhang D. (My University, 2004)
In order to investigate imaging properties of various magnetotelluric interpretation parameters over complicated models, we carried out numerical model calculations, where the models contained a 3D near-surface (“shallow”) part and a 3D or 2D deep part. Various alternatively defined magnetotelluric responses, all of them based on rotational invariants of the magnetotelluric impedance tensor were considered. Then we calculated correlation coefficients between all these MT responses, and the characteristic geometrical parameters of the subsurface models, considered as a composition of “shallow+deep” elements. A systematic behaviour, similar to that had been observed in 1D situation was found: det(Re Z), Re det(Z) based apparent resistivity has the largest depth of investigation and the best lateral resolution. Furthermore, besides the phase, the Re det(Z) (a twin-parameter of the phase) seems to give the most direct response about deep structures. In presence of 3D near-surface inhomogeneities the most surprising result is that there are narrow period windows, where the deep model can be directly seen in the Re det(Z) and in the phase responses.